Socio-psychological factors of students` satisfaction in the context of digitalization of education during the COVID-19 pandemic and self-isolation - I. E. Sokolovskaya (Цифровая социология)
As you know, digitalization of many aspects of modern society became relevant in the XX1 century for most developed countries. This process is also typical for the Russian Federation, and it has received a special acceleration during the current period of the COVID-19 pandemic. The Rapid development of digitalization is now taking place in the field of education, where distance learning is becoming one of the Central forms. This impetuosity has created a number of problems, both organizational and psychological, since the real reality has not yet been fully prepared for radical changes in both the teaching methodology and the methods of obtaining knowledge by the student audience. Accordingly, this transformation of such an important social sphere as education requires the efforts of representatives of many scientific disciplines, including philosophers, sociologists, cultural scientists, and psychologists. The latter, in addition to theoretical justifications, conduct a number of empirical studies on the psychological adaptability of young people studying to new conditions. One of them is the proposed study, which is based on the assumption that the level of satisfaction with work in the distance format of students during the period of self-isolation depends a lot on the degree of their subjective well-being. The socio-psychological factors that characterize the subjective well-being of students in this situation include: skills for distance learning, satisfaction with the results of this form of education, maintaining relationship with classmates, and the effectiveness of remote interaction with teachers. The empirical part of the study involved 100 students of student age. It has been revealed that the educational environment with a low level of quality (lack of electronic equipment on self-isolation, necessary for providing distance learning) and uncoordinated contacts with teachers and classmates, can negatively affect some components of satisfaction with distance education of students.